Women, travel, and writing in the interwar era - Hoag, Ann Catherine, author.
1 online resource
Keywords: "Women, Travel, and Writing in the Interwar Era engages feminist, temporal, and narrative theories to offer fresh examinations of interwar era accounts by women about travel and movement, and considers the use and limitations of time as a subversive force in their texts. This book makes a significant contribution to the under-examined study of women's travel writing between the wars, and synthesizes and applies a variety of feminist, narrative and postcolonial theories to excavate new understandings of the intersection between women, travel, and time in writing. The book studies the emergence of the aviatrix after the Great War and moves through to the representations of war in women's travel on the brink of World War Two. Each chapter offers a unique theoretical framework and examines how experiences of time impact perceptions of women's bodies and identities, their engagement with history and discourse, and the problematic influence on colonialism. Women, Travel, and Writing in the Interwar Era is essential reading to any student or researcher in the field of women's travel writing, as well as scholars of gender studies, war and interwar history, and cultural heritage"--